ON THE IMPORTANCE OF INTUITIONS IN POLITICAL PROCESSES IN THE AGE OF POLITICAL APATHY - Prodanović, Srđan (Politeia, 2025)
The paper explores the theoretical importance of intuitions in political processes, especially in the moments when there is a crisis in the reproduction of the dominant social norms. In this regard, particular attention is paid to the fact that today’s social institutions and conventional political organizations have largely lost their authority, which in turn has led to political apathy and the rise of post-political attitudes. Political intuitions, often based on experience and unconscious associations, can therefore play the key role in radical forms of democracy, most notably in times of crisis. The paper focuses on the difference between everyday political intuitions and intuitions about politics, emphasizing their importance in shaping public discourse and political decisions.